Ecological Amplitude and Regeneration of Medicinally Important Threatened Trees in the Central Western Ghats - Mathachen, Georgi P.; Vasudeva, R.; Gowda, H. C. Hombe; Ganeshaiah, K. N.; Uma Shaanker, R. (Indian Forester, 2004)
The central part of the Western Ghats (i.e. Uttara Kannada District of Karnataka) was surveyed for tree species and regeneration using belt transects. Medicinally important trees were more in disturbed evergreen forests while undisturbed evergreen forests had proportionately more threatened species. Out of total 19 species of medicinally important threatened trees recorded , only Knema attenuata , Garcinia gummigutta and Artocarpus hirsutus showed a wider ecological amplitude with presence in disturbed and undisturbed evergreen forests. All other species were either confined to undisturbed forests or were rare in both types. Most of the threatened medicinal trees showed decrease in abundance in the disturbed evergreen forests. Species for which seeds or fruits are extracted like Myristica malabarica , Garcinia sp. , Hydnocarpus pentandra etc. there was a lack of adequate regeneration compared to density of trees and are at double disadvantage of habitat loss and regeneration loss.